Reclaiming subjectivity through the maternal abject in Janie Chang’s three souls - Chin, Koon Poh; Mohammad Ewan Awang,; Arbaayah Ali Termizi,; Florence, Toh Haw Ching (Penerbit Universiti Kebangsaan Malaysia, 2023)
Three Souls by Janie Chang focuses on a changing transformative time in China’s history—the 1930s. During this period, China was experiencing political and societal shifts that prompted gender equality movements. Song Leiyin, the female protagonist in Three Souls, embodies the experiences of women during this period. She is an ambitious and desiring woman who lives in a family and society that restricts women's roles and abilities. As a woman with aspirations and desires, Song Leiyin is perceived as a threat to traditional values and paternal authority. In her journey towards reclaiming her subjectivity, Song Leiyin encounters many obstacles that force her to confront and challenge the patriarchal structures that oppress her. Despite the challenges, Song Leiyin manages to break free from the patriarchal constraints by reconnecting with her maternal drives. Julia Kristeva’s theory of abjection provides an analytical framework to explore the ways in which Leiyin experiences abjection and the consequences of confronting her abject desires. While commonly associated with the abject, this study argues that the maternal can be a site of resistance and empowerment. By embracing the maternal abject, women can assert their agency and break free from oppressive norms.